An innovative approach to manage prosumers in smart grid - Rathnayaka, Dinusha; Potdar, Vidyasagar; Kuruppu, S. (Springer, 2011)
Smart Grid (SG) achieves bidirectional energy and information flow between the energy user and the utility grid, allowing energy users not only to consume energy, but also to generate the energy and share with the utility grid or with other energy consumers. This type of energy user is called the "prosumer". The sustainability of the SG energy sharing process depends on its participating prosumers. Hence the prosumer management schemes are crucial within the energy sharing field. However, the existing literature on SG energy sharing has shown little attention on prosumer participation and management. The contribution of this paper is twofold. First we critically analyze the prosumer management schemes used by existing approaches and identify the open research issues. Second, we introduce a novel concept to manage the prosumers in the form of goal oriented virtual prosumer-communities and we discuss the aspects of prosumer-community formation, growth and overall management. The main significance of this approach is that the prosumer-communities facilitate the prosumers with similar interest to join together and increase the quantity of energy to be auctioned to the SG and accordingly increase the bargaining power in the energy market. In addition, the prosumer communities can attain more sustainable energy sharing process in long-term.